Placement breakdowns in long‐term foster care – a regional Swedish study. Issue 1 (9th October 2014) - Vinnerljung, Bo; Sallnäs, Marie; Berlin, Marie
Abstract: We used a regional sample of children in long‐term foster care to investigate the prevalence of placement breakdown in adolescence, and to assess risk factors/risk markers for placement disruption. The sample consisted of all 136 foster children in the region, born 1980–1992, who on their 12th birthday had been in the same foster family for at least 4 years. They were followed in case files until date of disruption or their 18th birthday. Data on conditions before and during placement were retrieved from case files, and analysed in bi‐ and multivariate models. Results showed that one in four placements broke down in adolescence. The median child who experienced a breakdown was 14 years old, and had been in the same foster home for more than 10 years. Prominent risk factors were (i) being placed after age 2 and (ii) having a birth sibling in the same foster home. We also uncovered strong risk markers that can be viewed as precursors of placement disruption. When the child or the foster parents repeatedly over time expressed dissatisfaction with the placement, this ended with a placement breakdown in 60% of cases. Implications for practice are discussed.